Lebanon Economic Monitor, Spring 2013 : Growing Tensions in a Resilient Economy - World Bank (Washington, DC, 2015)
The Lebanon Economic Monitor provides an update on key economic developments and policies over the past six months. It also presents findings from recent World Bank work on Lebanon. The political standoff combined with an escalating Syrian conflict hampered growth in 2012, and is projected to continue doing so through the first half of 2013. Economic growth in 2012 is estimated to have decelerated to 1.4 percent due to a weak second half of 2012 following a downturn in the security situation. The major fiscal expansion that took place in 2012 is creating fiscal challenges for 2013, particularly in the context of a promised increase in public salaries. The fiscal expansion, measured by the change in the central government s primary fiscal balance, reached a staggering 4.6 percentage points of GDP in 2012. The overall fiscal deficit reached 9.4 percent of GDP in 2012. Inflationary pressures rose despite tepid economic activity. Headline inflation accelerated notably in the second half of 2012. Core inflation has also been on an upward trend, reaching 5.3 percent by end-2012. Domestically, inflationary pressures can primarily be attributed to (i) increases in disposable income in early 2012 due to the increase in the minimum wage and public sector salaries cost of living adjustment; and (ii) a cumulative output gap that remains positive following above-potential growth in 2007-2010. The conflict in Syria, a country that is closely linked, both through historical, social and economic ties to Lebanon has created a humanitarian crisis of enormous scale. While Lebanon is to be commended for its openness to Syrian refugees, the conflict is severely and negatively impacting the Lebanese economy. The largest impact arises through the insecurity and uncertainty spillovers and touches at the heart of Lebanon s societal fabric.